Response of primed rice (Oryza sativa L.) seeds towards reproductive stage drought stress - Mohd Syahmi Salleh,; Mohd Shukor Nordin,; Adam Puteh,; Rozilawati Shahari,; Zarina Zainuddin,; Mohamad Bahagia Ab-Ghaffar,; Noraziyah Abd Aziz Shamsudin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Seed priming could be promoted as a potential alternative in alleviating drought stress challenges in rice cultivation. The present study was conducted as an attempt to verify potential performance of seed priming in improving seedling growth and harvestable grain yield of rice under reproductive stage drought stress (RS). Seed treatments involved were non-primed seeds as control (T1), hydro-primed (T2) and osmo-primed at -1.0 mPa with polyethylene glycol (PEG6000) (T3). Reproductive stage drought stress (RS) was imposed at soil water potential lower than -60 kPa. The well-watered plants served as control of the experiment. In general, seedling growth of T3 was better than T2 and T1 for all growth parameters in both planting seasons. Yield components were significantly lower in RS as compared to well-watered treatment (WW). The agronomic performance of primed seeds in T2 and T3 were not significantly different with T1 under both RS and WW for both planting seasons. As a conclusion, seed priming treatments used in this study was ineffective in improving agronomic performance of rice under RS. Therefore, other alternatives such as development of drought tolerant rice should be highly emphasized in order to minimize the impact of drought on growth and yield of rice plant.